EFFECT OF LIGHT FLUCTUATIONS ON GROWTH RATE OF THALASSIOSIRA SP. - Budi Rianto Wahidi; Tri Ari Setyastuti; Nisa Hakimah (Jurnal Perikanan Unram, 2024)
Thalassiosira sp. is Thalassiosira sp. is a diatom and used as a natural feed source in shrimp farming. Apart form naturally, Thalassiosira sp. can also be grown or cultured artificially on a laboratory scale using light. The purpose of this study was to determine the growth rate of Thalassosira sp. cultured on a laboratory scale with different fluctuations or periods of exposure to light. The study was carried out by differentiating the light and dark time periods for Thalassiosira sp. cultures, 0 hours: 24 hours; 6 hours : 18 hours; 12 hours : 12 hours and 18 hours : 6 hours. Data analysis used the ANOVA test, followed by the Games-Howell test to determine the best exposure time periodization. The light-dark time period of 12 hours : 12 hours was gained the optimum average growth rate in this study (2.5875 x 105 cells/ml), which was obtained on the 6th day after the initial culture. diatom and used as a natural feed source in shrimp farming. Apart form naturally, Thalassiosira sp. can also be grown or cultured artificially on a laboratory scale using light. The purpose of this study was to determine the growth rate of Thalassosira sp. cultured on a laboratory scale with different fluctuations or periods of exposure to light. The study was carried out by differentiating the light and dark time periods for Thalassiosira sp. cultures, 0 hours: 24 hours; 6 hours : 18 hours; 12 hours : 12 hours and 18 hours : 6 hours. Data analysis used the ANOVA test, followed by the Games-Howell test to determine the best exposure time periodization. The light-dark time period of 12 hours : 12 hours was gained the optimum average growth rate in this study (2.5875 x 105 cells/ml), which was obtained on the 6th day after the initial culture.